Implementacion del control interno en las pymes (2018)
In order for semes to establish their mission and vision, i proposed a guide for de implementation of a control system, with the purpose that they can view their growth, success and business development the lack of implementation of a system does not allow the aims of the organization, smes are the economic of the country: but has many weakenesses which make them less productive, traders create companies, but do not plan, they do not project, they do not have a clear methodology, even less proposed goals of how they will achieve it if the SMEs only focus on producing and not observing where the market is going which would cause SMEs to liquidate, making this clear for the development of this research. Make a conceptualization of what was the internal control in Colombia, its regulatory framework, diagnostics of how to exercise, determine, design internal control in SMEs and opinion n Contributions from different authors, concluding that SMEs need to know where they want to go, what their objectives are and what to do to achieve them.